Analyzing Market Manipulation in Kids and Consequential Parental Guilt from the Denial of Advertised Products - Dua, Ananya (Universitas Pendidikan Indonesia (UPI), 2022)
With the rise of technology, market manipulation among kids – the intenful propaganda to skew sales – has risen significantly as well. Companies advertised as ‘for kids’ are deliberately pushing out content towards these impressionable children to bait them, or rather their parents, into buying kids advertised items. This study recognized, however, that not all parents fall for this scheme and some often deny their children these products. It aimed to study the causes that propelled parents to deny their children these products, and whether the parents felt any guilt after the fact. It was hypothesized that parents who denied products due to monetary concerns would associate guilt with this act, over their inability to pay for all of their child’s wishes, whereas those who denied items for the wellbeing of their child associated no guilt due to their conviction that these steps were for their child’s benefit. The study analyzed publicly available data on parents and their reaction to these constant advertisements and concluded results in support of the hypothesis – there was a moderately strong association evident between the reason for denial and parental guilt associated as a consequence. The results of this study can help provide insight into the thought processes of parents as well as hint at growing parenting trends, to better inform development of resources.